The Cocoanuts [videorecording (Blu-Ray)] - Ryskind, Morrie, 1895-1985; Dumont, Margaret, 1882-1965; Marx, Groucho, 1890-1977; Marx, Harpo, 1888-1964; Marx, Chico, 1887-1961; Marx, Zeppo, 1901-1979; Kaufman, George S. (George Simon), 1889-1961 (Universal Pictures Home Entertainment, 2023)
The legendary Marx Brothers Groucho, Harpo, Chico, and Zeppo made their motion picture debut in the outrageously funny adaptation of their Broadway play The Cocoanuts. Groucho portrays the owner of the Hotel de Cocoanut who tries to fleece everyone from innocent bellboys and bellgirls to wealthy society matron Mrs. Potter. Chico and Harpo play resort hotel con men who arrive with empty suitcases they plan to fill by robbing guests. Featuring elaborate musical productions with music by Academy Award winner Irving Berlin, this comedy treasure includes some of the Marx Brothers' best stage routines, such as Groucho's land auction, the excruciatingly funny 'viaduct' dialogue, and Polly Potter's engagement party.